Genetic diversity, evolutionary relationships and conservation of southern African Labeo fishes in relation to water management - Ramoejane, Mpho (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2017)
Labeo spp. are large, herbivorous fishes that are important components of aquatic ecosystems and are a high conservation priority in South Africa. This thesis contributes to determination of conservation priorities for Labeo umbratus (Smith 1841) by resolving the taxonomic status of this species in the evolutionary context of southern African Labeo spp., assessing the presence of unique lineages in historically isolated river basins, and assessing the threat of intra- and interspecific hybridisation associated with introductions. Phylogenetic analyses of five DNA sequence data sets (cytochrome c oxidase subunit I gene [COI], cytochrome b gene [Cyt b], Recombination activating gene 1 [Rag1], COI+Rag1 and COI+Cyt b+Rag1) showed that the Labeo umbratus group (sensu Reid, 1985), which comprises the species Labeo umbratus, Labeo capensis (Smith 1841), Labeo seeberi Gilchrist and Thompson 1911 and Labeo rubromaculatus Gilchrist and Thompson 1913, is monophyletic, morphologically distinct and geographically disjunct from other African Labeo spp. groups except in the Tugela River system were L. rubromaculatus co-occurs with Labeo molybdinus Du Plessis 1963. Phylogeographic analysis of mitochondrial DNA (Cyt b) sequence data demonstrated that the populations of the L. umbratus from the Orange and the southward-flowing river systems are reciprocally monophyletic and were identified as evolutionary significant units. The populations in the southward-flowing river systems were further divided into southwestern (Gourits and Gamtoos) and southeastern (Sundays, Bushmans, Great Fish, Keiskamma, Buffalo and Nahoon) polyp hyletic sublineages. Four management units (Gourits Basin; Gamtoos Basin; Sundays+Bushmans+Great Fish River Basins; and Keiskamma+Buffalo+Nahoon River Basin) were not reciprocally monophyletic but were proposed on the basis of containing unique haplotype frequencies for conservation purposes. To evaluate the threat of hybridisation to the genetic integrity of L. umbratus, the occurrence of Labeo umbratus x L. capensis hybrids was investigated using mtDNA Cyt b and nDNA S7 intron sequence data and morphological data. Genetic evidence for interspecific hybridisation was detected for populations in two impoundments, Hardap Dam (Orange River Basin) and Darlington Dam (Sundays River Basin, Eastern Cape, South Africa). Some putative hybrids were identifiable morphologically on account of intermediacy between the parental species in meristic and morphometric characters. Translocation via direct stocking (Hardap Dam) or via an inter-basin water transfer scheme (Darlington Dam) was identified as a driver for hybridisation. Introductions associated with an inter-basin water transfer scheme has resulted in introgression between the previously isolated Orange River and southern lineages of L. umbratus. Further translocation of fish from these affected areas to non-contaminated river systems and impoundments such as Kat River (Great Fish River) and Slagboom (Sundays River) should be avoided.
Keywords: Uncatalogued